RELAÇÃO ENTRE ATIVIDADES EXPERIMENTAIS E O SETOR SUCROALCOOLEIRO NOS LIVROS DIDÁTICOS DE CIÊNCIAS DA NATUREZA E SUAS TECNOLOGIAS - Vagner Torres dos Santos (2021)
The alcohol theme is significant in the national scenario for education in regions with this economic profile. This is confirmed by Brazil's position on the world stage, where it stands out for being one of the largest producers of sugar and ethanol in the world. In some economic regions it is more present in the Southeast and as is the case in the Midwest of the country. Teaching materials, such as books, are not developed taking into account the specificities of each region, since the National Textbook Program (PNLD) covers the national level and the choice of approved Textbooks (LDs). The present work aimed to carry out the analysis of Chemistry experiments, in LDs of Natural Sciences and Technologies (LDCNT) and their relations with the sugar and ethanol sector. The interest to carry out this dissertation came from the researcher's observation of his experience in the sugar and alcohol industry and as a Chemistry teacher. To achieve the objective of the dissertation, it was necessary to identify the LDs belonging to the PNLD-2021, as well as the Chemistry experiments in the books, to then proceed with a comparative analysis. With the results of the dissertation, it was possible to propose a product, Roadmap of Experimental Chemistry Activities on the Sugar-Alcohol Sector for High School, as a tool for teachers in the teaching of Chemistry. To carry out this work, 42 LDCNTs were analyzed, covering a total of 82 experimental activities of Chemistry, and for the analysis, 10 questions were asked that relate the Experimental Activities of Chemistry with the sugar and alcohol sector, as well as the relationship with the Curriculum of Mato Grosso do Sul. The data are not legal, in addition to the distribution of experimental activities during the LDs, they are presented in a very superficial way, presenting a very superficial relationship with the sugar sector. These gaps such as skills to be offered, economics and the relationship with the student, where they were offered to economic teachers and culture, led the teacher to be an extra tool for Chemistry teachers in these regions, as the economy is a product to the product that provides to the student sugar and alcohol sector.